A power log-Dagum distribution: estimation and applications. Issue 5 (4th April 2019) - Bakouch, Hassan S.; Khan, Muhammad Nauman; Hussain, Tassaddaq; Chesneau, Christophe
ABSTRACT: Development and application of probability models in data analysis are of major importance for all sciences. Therefore, we introduce a new model called a power log-Dagum distribution defined on the entire real line. The model contains many new sub-models: power logistic, linear log-Dagum, linear logistic and log-Dagum distributions among them. Some properties of the model including three different estimation procedures are justified. The model exhibits various shapes for the density and hazard rate functions. Moreover, the estimation procedures are compared using simulation studies. Finally, the model with others are fitted to three data sets, and it shows a better fit than the compared distributions defined on the real line.